Activation of hypothalamic oxytocin neurons following tactile stimuli in rats. (23rd July 2015) - Okabe, Shota; Yoshida, Masahide; Takayanagi, Yuki; Onaka, Tatsushi
Highlights: Stroking stimuli activated hypothalamic paraventricular oxytocin neurons. Rats emitted 50-kHz ultrasonic vocalizations during stroking stimuli. Pleasant stroking is thought to activate hypothalamic oxytocin neurons. Abstract: Gentle touching or stroking has anxiolytic actions and contributes to the establishment of an intimate relationship between individuals. Oxytocin administration also has anxiolytic actions and facilitates social behaviors. In this study, we examined effects of stroking stimuli on activation of oxytocin neurons and emission of 50-kHz ultrasonic vocalizations, an index of positive emotion, in rats. The number of oxytocin neurons expressing Fos protein was increased in the hypothalamus, especially in the dorsal zone of the medial parvicellular part of the paraventricular nucleus. The number of 50-kHz ultrasonic vocalizations was also increased. These findings suggest that pleasant sensory stimuli activate hypothalamic oxytocin neurons.